23. ASSESSMENT OF THE RESULTS OF NURSING CARE FOR PATIENT WITH COPD AT THE DEPARTMENT OF INTERNAL MEDICINE NO 1, SAINT PAUL GENERAL HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2023)
Objective: To evaluate the results of treatment and care for patients with COPD exacerbations at theDepartment of Respiratory Internal Medicine - Saint Paul General Hospital.Methods: 121 subjects with COPD were monitored and assessed the nursing care process uponadmission and discharge.Results: The proportion of patients ≥ 60 years old (85.8%); men 61.5%; COPD duration of 2 to 5years 56.4%. The smoking rate was 70.5%, tobacco 47.4%, pipe tobacco 47.4%, and quit smokingaccounted for 63.1%. Upon admission and discharge, patients with COPD receive adequate careregarding vital signs and health status, nutritional care and rehabilitation support, and healtheducation. The rate of patients receiving good care at the time of admission was 87.4%; at the timeof discharge was 91.6%.Conclusion: Patients with COPD receive adequate care regarding vital signs and health status,support nutritional care, and rehabilitation function during hospitalization and discharge. Mostpatients receive good nursing care.
Keywords: Nursing care, COPD, healthcare.